Correction: Alamri et al. Enhancement of the Protective Activity of Vanillic Acid against Tetrachloro-Carbon (CCl4) Hepatotoxicity in Male Rats by the Synthesis of Silver Nanoparticles (AgNPs). Molecules 2022, 27, 8308 - Eman S. Alamri; Haddad A. El Rabey; Othman R. Alzahrani; Fahad M. Almutairi; Eman S. Attia; Hala M. Bayomy; Renad A. Albalwi; Samar M. Rezk (Molecules)
In the original publication [...]